Pengaruh Kontribusi Sektor Pariwisata dan Industri Jasa Lainnya Terhadap PDRB Kabupaten Lampung Selatan - arinda, rara (Universitas Negeri Surabaya, 2023)
Gross Regional Domestic Product (GRDP) indicates economic growth in an area caused by various sectors. One of them is the Tourism sector, and other successful industries, especially in South Lampung Regency. This study aims to analyze the effect of the tourism sector and other service industries on the GRDP of South Lampung Regency for the 2018-2022 period. The type of research used is quantitative research with the analysis technique used, namely multiple linear regression analysis using SPSS version 20. The results of the analysis show that the tourism sector and other service industries partially and simultaneously affect GRDP. Therefore, all hypotheses in this study are accepted.